2004
DOI: 10.1007/s00268-004-7611-1
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Effects from Treatment with Bisphosphonate and Surgery in Patients with Primary Hyperparathyroidism

Abstract: Patients with primary hyperparathyroidism (pHPT) are sometimes treated with bisphosphonates (BPs) as an alternative to surgery despite sparse documentation of the efficacy in this disorder. It is therefore of interest to study the biochemical effects from BPs in patients with pHPT. A series of 21 pHPT patients with serum calcium levels > 2.8 mmol/L were included. One month before surgery the patients underwent intravenous infusions of 30 to 40 mg pamidronate. Study parameters were total and ionized serum calci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 34 publications
0
3
0
1
Order By: Relevance
“…Serious adverse effects of bisphosphonates have been increasingly reported, including acute systemic inflammatory reaction, ocular inflammation, renal failure, nephrotic syndrome, electrolyte imbalance and osteonecrosis of the maxilla and mandible 26,27 . In the study of Jansson et al ., brief and limited use of bisphosphonates for PHPT patients was advised 28 . Our study shows the refractoriness to bisphosphonates in preventing hypercalcaemic crisis in 3 (case 12–14) out of 14 group 2 patients.…”
Section: Discussionmentioning
confidence: 72%
“…Serious adverse effects of bisphosphonates have been increasingly reported, including acute systemic inflammatory reaction, ocular inflammation, renal failure, nephrotic syndrome, electrolyte imbalance and osteonecrosis of the maxilla and mandible 26,27 . In the study of Jansson et al ., brief and limited use of bisphosphonates for PHPT patients was advised 28 . Our study shows the refractoriness to bisphosphonates in preventing hypercalcaemic crisis in 3 (case 12–14) out of 14 group 2 patients.…”
Section: Discussionmentioning
confidence: 72%
“…Pamidronate in several studies showed lowering of the serum calcium. However, due to limited time frame, no changes in BMD nor complications were reported [94][95][96][97][98][99][100]. Clodronate use was associated with lowering of the serum calcium [101][102][103].…”
Section: Bisphosphonatesmentioning
confidence: 99%
“…В других работах ни у кого из пациентов не выявлено нарушения концентрационной функции почек, в том числе в ходе пробы с сухоядением. Авторы предполагают, что снижение концентрационной функции почек характерно только для тяжелых форм ПГПТ, но не исключают того, что оно может развиться при более длительном течении заболевания [14,15]. К сожалению, в проанализированных работах нет единого критерия оценки состояния концентрационной функции почек (оценивалась осмоляльность утренней мочи и осмоляльность мочи в ходе проведения различных функциональных проб).…”
Section: '2015unclassified